2015
DOI: 10.14198/jhse.2015.10.proc1.42
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between isokinetic muscle strength and 100 meters finswimming time

Abstract: Kunitson, V., Port, K., & Pedak, K. (2015). Relationship between isokinetic muscle strength and 100 meters finswimming time. J. Hum. Sport Exerc., 9(Proc1), pp.S482-S489. Finswimming is a sport where athlete uses one big monofin to produce propulsion. The purpose of this study was to describe relationship between isokinetic strength of different muscle groups and 100 meters finswimming time. Study questions was: what muscle groups have relationship with finswimming time. Methods: 17 international level monfin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The above outcomes are in accordance with the study that reported an inverse relationship between isokinetic knee extension force and mono-fin swimming 100 m time [25]. However, some studies indicated that isokinetic force variables were not associated with swimming performance [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…The above outcomes are in accordance with the study that reported an inverse relationship between isokinetic knee extension force and mono-fin swimming 100 m time [25]. However, some studies indicated that isokinetic force variables were not associated with swimming performance [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…This characteristic is what makes athletes have different kick frequencies and give different responses when getting an increase in monofin stiffness. So Kunitson et al, (2015) argue that the formation of athletes to specialize in the number 100 Meter…”
Section: Comparison Of Hard and Extra Hard Stiffness To Kick Frequencymentioning
confidence: 99%